INJURY PATTERN OF BLUNT TRAUMA CASES IN SLEMAN BASED ON HDSS IN 2019 - Idha Arfianti Wiraagni; Abidzar Al Ghifari; Hendro Widagdo; Martiana Suciningtyas Tri Artanti (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2025)
ABSTRACTBlunt trauma, also known as blunt force trauma kind of injury that arises from the high-power impact of the human body with a dull object. It come from the results of a physical attack with a blunt object, or even an accidental event such as a transportation crash. There are four categories for blunt trauma, contusion, abrasion, laceration, also fracture. Health and Demographic Surveillance System (HDSS) Sleman is a surveillance system that keeps a demographic mapping, especially in the health sector. It works by hiring respondents from every subdistrict and refreshing them periodically. By analyzing the pattern of the injury incidences using both univariate and bivariate analysis, we are able to gain a deeper understanding about the prevalence and injury prevention in the future. The purpose of this study is to determine the pattern of blunt force injury cases in Sleman based on HDSS data from 2019. A descriptive study is obtained by using the secondary data provided by HDSS Sleman about blunt trauma cases that occurs in the Sleman region in 2019. The parameters that became a pattern category for this study are age, gender, level of education, type of blunt trauma cause of injury From total sample of 612 respondents, people aged 19 to 59 leads the number with 312 cases (50.9%) recorded. Male respondents came out with 53.1% of total cases. The incidences mostly occur in respondents with basic education level with 236 cases (38.5%). Back injury correlates with loss of sensory with the p-value of 0.024, and lower extremity correlates with permanent wound with the p-value of 0.042. It mostly found in Motorcycle accidents with 294 out of 612 total cases. Significant correlations were found between the site and the type of injury such as head injuries with lacerations (p <0.001) and chest injuries with fractures (p=0.040). Study conducted based on HDSS Sleman data in 2019 shows a pattern of blunt trauma injury cases. It mostly occurs in productive age adult group and male. People with lower education levels have higher injury risk. Specific injury types are linked to particular trauma sites and mechanism with traffic motorcycle accidents being a primary cause based on mechanism. Head injuries often involve lacerations, chest injuries commonly involve fractures, upper extremity injuries correlate with lacerations and fractures, and lower extremity injuries mostly end with fractures and contusions/abrasions.ABSTRAKTrauma tumpul adalah jenis cedera yang timbul akibat benturan berkekuatan tinggi pada tubuh manusia dengan benda tumpul. Kejadian trauma tumpul pada berbagai kasus trauma sangatlah tinggi. Health and Demographic Surveillance System (HDSS) Sleman merupakan sistem surveilans yang menyimpan pemetaan demografi khususnya di bidang kesehatan. Tujuan penelitian ini adalah untuk mengetahui pola cedera benda tumpul di Sleman berdasarkan data HDSS tahun 2019. Penelitian deskriptif dilaksanakan dengan total sampel sebanyak 612 responden, kelompok usia 19 hingga 59 tahun muncul dengan 312 kasus (50,9%). Responden laki-laki keluar sebanyak 53,1% dari total kasus. Kejadian terbanyak terjadi pada responden dengan tingkat pendidikan dasar sebanyak 236 kasus (38,5%). Cedera punggung berkorelasi dengan hilangnya sensorik dengan nilai p 0,024, dan ekstremitas bawah berkorelasi dengan luka permanen dengan nilai p 0,042. Kecelakaan terbanyak terjadi pada kecelakaan sepeda motor dengan jumlah 294 kasus dari total 612 kasus. Ditemukan korelasi yang signifikan antara lokasi dan jenis cedera seperti cedera kepala dengan laserasi (p <0,001) dan cedera dada dengan patah tulang (p=0,040). Pada studi ini, paling banyak terjadi trauma tumpul pada kelompok dewasa usia produktif dan laki-laki. Orang dengan tingkat pendidikan yang lebih rendah memiliki risiko cedera yang lebih tinggi. Kecelakaan lalu lintas sepeda motor menjadi penyebab utama cedera berdasarkan mekanismenya. Cedera kepala sering disertai laserasi, cedera dada umumnya disertai patah tulang, cedera ekstremitas atas berkorelasi dengan laserasi dan patah tulang, dan cedera ekstremitas bawah sebagian besar berakhir dengan patah tulang dan memar/abrasi.